Enhanced second and third harmonic generations of vertical and planar spiral MoS2 nanosheets. (30th June 2017) - Zhang, Jinlin; Ye, Mingxiao; Bhandari, Shiva; Muqri, Aeshah Khudaysh M; Long, Fei; Bigham, Sajjad; Yap, Yoke Khin; Suh, Jae Yong
Abstract: Molybdenum disulfide (MoS2 ), as one of the atomically thin two-dimensional transition metal dichalcogenides has novel layer-dependent optical and electronic properties, which make it competitive for potential applications in optoelectronics. Here, we report chemical vapor deposition growth of vertically-standing and planar spiral MoS2 nanosheets. These vertical spiral MoS2 nanosheets are formed by the compression between planar spiral MoS2 in a close proximity. Both structures have a polytype 3R stacking with broken inversion symmetry, exhibiting strong second and third harmonic generations.